(untitled) (Research, Society and Development, 2021)
The present work aimed to evaluate the passion fruit residues (shells and seeds) as alternative adsorbents for the treatment of effluents contaminated by Red Quimicryl GRL dye, test the effect of ionic strength and pH on the efficiency of the adsorption process and finally check whether the desorption process is feasible. The adsorption process was carried out in a fixed bed column with the adsorbent in natura and treated with NaOH (sodium hydroxide). The effect of ionic strength was evaluated using together the dye solution NaCl (sodium chloride) at different concentrations, the pHs evaluated were 2, 5, 7 and 12, the desorption process was evaluated using HCl (hydrochloric acid) as an extracting solution. Thus, it was observed that the adsorption was favored by the biomass treated with NaOH, the effect of ionic strength influenced the adsorption process, and for the sample with 1.0 mol L-1 NaCl concentration, the adsorption process was advantageous, the pH directly influenced the process, and the higher the pH value the adsorption affinity increases, so the best pH tested was 12. The best biomass tested were passion fruit husks treated with NaOH with value of maximum adsorption capacity of 45.9 mg g-1 for the analyzed dye.